2019
DOI: 10.3390/jfb10030027
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Orbital Post-Traumatic Wall Defects by Custom-Made TiNi Mesh Endografts

Abstract: Repairs of orbital post-traumatic and extensive malignant defects remain a major surgical challenge, in view of follow-up outcomes. Incorrect surgical management of injured facial structures results in cosmetic, ophthalmic, and social aftereffects. A custom-made knitted TiNi-based mesh (KTNM) endograft was employed to overcome post-surgical complications and post-resected lesions of the orbital area. Preoperative high-resolution computed tomography (CT) imaging and CAD modelling were used to design the customi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…It is simply modified intraoperatively, to attach any desired shape/size for implantation, and can also be screw-fixed, providing a good supporting ability. The authors concluded that this method of reconstruction may be an attractive alternative to Ti-based meshes and plates in patients with enophthalmos, hypoglobus or diplopia, with good functional and cosmetic outcomes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is simply modified intraoperatively, to attach any desired shape/size for implantation, and can also be screw-fixed, providing a good supporting ability. The authors concluded that this method of reconstruction may be an attractive alternative to Ti-based meshes and plates in patients with enophthalmos, hypoglobus or diplopia, with good functional and cosmetic outcomes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the issues in the development of new modalities for reconstructive treatment in zygomatic complex fractures remain extremely actual. Analysis of the properties of metallic materials and alloys shows that alloys based on nickel-titanium alloys are the most compatible materials with body tissues, which is due to the delay of biological systems [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the features of the anatomical structure, the study of the structure of injuries to the MAP, a large number of classifications were created [14]. At the same time, the selection of features that must be taken into account presents a significant difficulty.…”
Section: Main Partmentioning
confidence: 99%
“…Porous and solid TiNi-based implants and their successful deployment in surgical treatments have encouraged insights for immediate and delayed rib-plasty in cancer patients. Experimental and clinical studies with promising results have demonstrated successful integration of TiNi implants with the formation of regenerated tissues, which anatomically and physiologically restore the injured area [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Recently, porous SHS-TiNi alloys have been reported [ 31 ] to have some features that significantly distinguish them from those manufactured by other methods of powder metallurgy.…”
Section: Introductionmentioning
confidence: 99%